MORPHOLOGICAL ERRORS ON ARAB-INDONESIA TRANSLATION TEXT USING GOOGLE TRANSLATE/ KESALAHAN MORFOLOGIS PADA TEKS TERJEMAHAN MESIN PENERJEMAH GOOGLE TRANSLATE - Ilmi, Ipti Karul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This research aims to analyze the morphological errors in the text of the Indonesian-Arabic translation translated by the translator engine Google Translate. This study used a qualitative research design with content analysis. Google Translate machines translate some of the texts of Nahwa An-Nur by Sheikh Hasan Albana, and this is the source of data in this study. The results of the study show there are three methods of translation on Google Translate, namely word for word, literal, and free translation methods. There are eight mistakes in translating GT, in terms of the morphology of the translation machine, Google Translate is more likely to expand meaning than the morphological angels themselves, so it is needed for more morphological explanations so that the target language can be achieved.